An Evaluation of Talent 4 . . .: A Programme to Identify Talent and Skills for Prisoners, Disadvantaged, Unemployed, and Vulnerable Groups - McGuire-Snieckus, Rebecca (International journal of offender therapy and comparative criminology, 2018)
Previous research suggests that the relationship between employment and recidivism is complex, with more support needed to facilitate employability motivation for sustained change. An arts-based programme designed to facilitate vocational self-determinism among prisoners with evidence of impact across three prisons in the United Kingdom was replicated and delivered to 234 prisoners and long-term unemployed participants from six European countries, to explore whether the findings from the previous evaluation would be replicated on a much larger scale. The research presented in this article found that supporting prisoners and the long-term unemployed to articulate employability goals had a positive effect on personal growth as well as understanding of individual strengths and weaknesses with respect to work, employment, problem solving, and thinking styles. Future research might explore the longer term impact on employment and recidivism.